Volume 1: Turbomachinery 1990
DOI: 10.1115/90-gt-075
|View full text |Cite
|
Sign up to set email alerts
|

LDV Measurements of Turbulent Stresses in Radial Turbine Guide Vanes

Abstract: The results of Laser Doppler Velocimetry (LDV) measurements, in particular, turbulent stresses in radial turbine guide vanes are presented in this paper, in order to provide experimental data for the numerical predictions. The flow velocities were measured at upstream, inside and downstream of the guide vanes for two different mass flow rates (0.2 lb/s “0.0907 kg/s” and 0.3 lb/s “0.1361 kg/s”) using a two-component LDV system. The results are presented as contour plots of turbulent stresses. The LDV system con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It should be pointed out that the losses in stator are not discussed because the stator is located at the upstream of shroud cavity, and there are little changes of the internal flow field in a favorable pressure gradient system. Early experimental investigations 30,31 showed that passage vortices know from axial turbines could not be found in the stator of radial turbine. Putra and Joos 32 argued that there exists an inflow vortex in the stator passage, which mainly causes the secondary vorticity in the circumferential direction.…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out that the losses in stator are not discussed because the stator is located at the upstream of shroud cavity, and there are little changes of the internal flow field in a favorable pressure gradient system. Early experimental investigations 30,31 showed that passage vortices know from axial turbines could not be found in the stator of radial turbine. Putra and Joos 32 argued that there exists an inflow vortex in the stator passage, which mainly causes the secondary vorticity in the circumferential direction.…”
Section: Resultsmentioning
confidence: 99%
“…Deviations of calculated flow angle and velocity distributions from the experiments in the trailing edge region are rapidly diminishing in the downstream direction due to intensive mixing. Additionally Eroglu and Tabakoff (1990) report about experiments concerning the turbulence stress within the vaned region. Because of flow inertia lower turbulence levels are revealed when the mass flow rate is increased.…”
Section: Investigations By Benson and Jacksonmentioning
confidence: 99%
“…It has a significant impact on the overall performance of the radial inflow turbine. On the study of the flow field structure and losses inside the ideal gas radial inflow turbine nozzle, an experimental study of the internal flow of radial inflow turbine nozzle using laser Doppler velocimetry was carried out by Hasan [5]. It showed that the internal flow of the nozzle has obvious three-dimensional characteristics; Putra [6] investigated the secondary flow phenomenon in radial turbine nozzles through numerical simulation.…”
Section: Introductionmentioning
confidence: 99%